Motivación terminológica y léxico médico: la red de relaciones semánticas y morfogenéticas entre malaria, paludismo y plasmodiosis. - Molina Sangüesa, Itziar (El Colegio de México, 2021)
This paper analyzes the semantic relationships established between a set of medical terms based on three axes headed by the synonyms malaria, paludismo and plasmodiosis. The terms documented are used in Spanish histories of medicine aimed at the general public and refer to an infectious disease transmitted by the bite of the Anopheles mosquito. At the same time, the paper identifies the morphogenetic mechanisms and the linguistic motivation of this medical terminology as well as studying its use from its earliest datings to the present day. In this way the paper offers a collection of data that has rarely been studied and that we believe can contribute to the diachronic reconstruction of the medical lexicon in Spanish. Its results indicate a progression from orography or climatology to microbiology and entomology in the names that, historically, have been given to this disease.